Governance of Banking Activity as a Mechanism to Combat Financial Corruption in Arab Countries" (Algerian banking system model) - Ben Abddulaziaz Sofyan; Ben ali Mohamed (Journal of Excellence for Economics and Management Research, 2017)
As banking institutions play an important economic activity as the main source of capital flow in the artery of any economy, the process of judging it is the basis for ensuring that it continues to function and achieve its objectives.  This study seeks to shed light on the role played by governance in raising the performance of banks and activating their role and integrity in the Algerian national economy.